Comparison between Heads of Nursing and Nursing Administration Students in the Sultanate of Oman regarding Education for Nurse Administrators - White, Gillian (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2012)
OBJECTIVE: To explore the future of nursing administration in preparation for a major review of the current curriculum in the one-year diploma in nursing administration at the Oman Specialized Nursing Institute (OSNI). METHODS: A two-part study explored 1) requisite roles, skills and competencies of the nurse administrator, 2) a leadership profile with two convenience samples: heads of nursing and nursing administration students. Each part was analysed separately; the two groups were then compared with the latter revealing similarities and differences. RESULTS: Heads of nursing were more likely to describe roles and be task-oriented, emphasising problem solving, whereas students focused on functions and processes. Both groups wanted nursing to be known for its code of professional conduct, and have an empowered nursing association. Leadership profile comparisons indicated heads of nursing were mature and practical whereas students were idealistic, with risk-taking tendencies. There was overall agreement that preparation for the nursing administration specialty should be at master’s level; however, all nurses should undertake a leadership and management course during their progression to senior positions. CONCLUSION: The vision of those preparing to enter and those already in leadership positions is for empowerment of the nursing profession in Oman. Thus there is a need for highly educated nurse leaders and managers in nursing administration to provide the driving force for change and sustained motivation. The current Nursing Administration Programme (NAP) needs to be upgraded and delivered at the master’s level for nurses specialising in nursing administration.